2004
DOI: 10.1158/1078-0432.ccr-031212
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk between Estrogen Receptor and Growth Factor Pathways as a Molecular Target for Overcoming Endocrine Resistance

Abstract: Introduced more than 100 years ago, endocrine therapy is still the most important systemic therapy for all stages of estrogen receptor (ER) -positive breast tumors. A major clinical problem limiting the usefulness of this therapy is tumor resistance, either de novo or acquired during the course of the treatment. Relatively new discoveries emphasize the complexity of ER signaling and its multiple regulatory interactions with growth factor and other kinase signaling pathways. Both genomic (nuclear) and nongenomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
293
1
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(311 citation statements)
references
References 42 publications
13
293
1
4
Order By: Relevance
“…Alterations in the PI3K/AKT pathway, mainly PIK3CA mutations, have been shown most frequent in the luminal subtypes, suggesting a crosstalk between ER and PI3K/AKT [3]. Aberrant PI3K/AKT signalling has been connected to poor response to anti-oestrogen therapies in several studies [20,[42][43][44][45][46][47][48][49][50]. In the present study, we showed PTPN2 gene loss as a new potential marker of endocrine resistance.…”
Section: Discussionsupporting
confidence: 62%
“…Alterations in the PI3K/AKT pathway, mainly PIK3CA mutations, have been shown most frequent in the luminal subtypes, suggesting a crosstalk between ER and PI3K/AKT [3]. Aberrant PI3K/AKT signalling has been connected to poor response to anti-oestrogen therapies in several studies [20,[42][43][44][45][46][47][48][49][50]. In the present study, we showed PTPN2 gene loss as a new potential marker of endocrine resistance.…”
Section: Discussionsupporting
confidence: 62%
“…This could indicate that tamoxifen does not completely block the action of E2 in some patients due to high levels of E2. Acquired tamoxifen resistance is believed to arise due to increased phosphorylation of the ER by growth factor signalling or due to increased expression of coactivators (Nicholson et al, 2004, Schiff et al, 2004. This means that tamoxifen acts as an agonist after long duration of treatment in some patients, and the question is how the resistant tumour cells will respond to high E2 levels after the completion of tamoxifen treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, non-genomic action of estrogen often includes ligand binding to the ER at the plasma membrane and follows the activation of signaling pathways. It has been demonstrated that several signaling kinases interacted with and were activated by the ER, including IGF-1R (insulin-like growth factor-1 receptor), Src, PI3K (phosphatidylinositol 3-kinase), MAPK (mitogen-activated protein kinase), protein kinases A and C and calcium pathways [65], EGFR (epidermal growth factor receptor) and ErbB-2, with non-genomic effects of the ER [66,67]. Furthermore, genomic and non-genomic mechanisms of action of ER are not mutually exclusive, but many interactions exist between these two modes [4].…”
Section: Discussionmentioning
confidence: 99%